Implementasi Gaya Komunikasi Joko Widodo dalam Berpolitik - Andi Budi Sulistijanto (Neolectura, 2022)
This research is based on Joko Widodo's communication style which is slightly different in his approach to political communication. As a political actor, Joko Widodo is able to mingle with various levels of society, from the people, religious leaders, to political institutions such as the DPR. The phenomenon in this study uses an interpretive paradigm to conduct a more in-depth study and analysis of Jokowi's political communication style. In order for the study to be more extensive and in-depth in revealing the phenomenon of Jokowi's political communication style, a qualitative approach is used. The purpose of this research study is as a means to answer the following research questions: 1) Knowing that political communication and Jokowi's persuasion as a political communicator is implemented in reducing political noise. 2) Knowing the characteristics of Jokowi's political communication style 3) Knowing the implementation and influence of Jokowi's political communication style in the harmonization of relations between the President and the DPR and NU Organizations 4) Knowing the findings of the uniqueness of Jokowi's political communication style as a new tradition in Indonesian politics. As for some research findings in examining the phenomenon of Jokowi's Political Communication Style, the researcher reveals that Jokowi's political communication style is populist, not long-winded, as it is. Jokowi likes to work a lot rather than talk too much. Jokowi uses a commoner style of communication and serves or what is called servant leadership because Jokowi's background comes from a simple family. With this communication style, Jokowi has given a sense of optimism and received a warm welcome by most of the Indonesian people so that he can unite the diversity that exists in the Republic of Indonesia